STRATEGI PENINGKATAN PEREKONOMIAN MASYARAKAT PADA MASA COVID-19 DI LANGKAT, BINJAI, DAN KARO - Yusdha, Nur Aflah; Mardziah, Ainun; Putra, Ilham Mirzaya (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: The global Covid-19 pandemic that hit every country in the world in 2020 has affected everyone's life. When the government enforces a policy of limiting activities to suppress the spread of the Covid-19 virus, the main impact on the economy that people rely on is almost all sectors in Indonesia. Moreover, the Covid-19 pandemic has resulted in a decline or slowdown in the economic sector in Indonesia. In order for SMEs in this sector to survive, they must be able to develop measures and strategies to improve the community's economy during the Covid-19 period in Langkat, Binjai, and Karo, and the purpose of this research is to help SMEs to improve from each product they produce, so that survive the pandemic. This study uses a comparative method of qualitative research methods, namely a qualitative approach that involves research procedures that produce descriptive information in the form of written or spoken language of individuals and observed behavior. Data collection techniques through observation, interviews and documentation. Qualitative analysis techniques were used for data analysis. This research uses source triangulation to get more accurate SMEs data. The results show that SMEs stakeholders need to implement the following strategies to survive the pandemic. This means using marketing through social media such as Instagram, Facebook and WhatsApp in collaboration with online transportation service providers such as Go-Food and Grab-Food, innovation in their products.Keywords: Strategy; Economy; Pandemic; SMEs. Abstrak: Pandemi global Covid-19 yang melanda setiap negara di dunia tahun 2020 sudah telah mempengaruhi kehidupan setiap orang. Ketika pemerintah memberlakukan kebijakan pembatasan kegiatan untuk menekan penyebaran virus Covid-19, dampak utama terhadap perekonomian yang tumpuan masyarakat hampir terjadi di semua sektor di Indonesia. Apalagi, pandemi Covid-19 yang mengakibatkan turunnya atau memperlambat dalam sektor ekonomi di Indonesia. Agar UKM di sektor ini dapat bertahan, mereka harus mampu mengembangkan langkah dan strategi peningkatan perekonomian masyarakat pada masa Covid-19 di Langkat, Binjai, dan Karo, dan tujuan dari penelitian ini adalah untuk membantu UKM dapat meningkatkan dari setiap produk yang mereka hasilkan, sehinga dapat bertahan di tengah Pandemi. Penelitian ini menggunakan metode komparatif metode penelitian kualitatif, yaitu pendekatan kualilatif yang melibatkan prosedur penelitian yang menghasilkan informasi deskriptif dalam bentuk bahasa tertulis atau lisan individu dan perilaku yang diamati. Teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Teknik analisis kualitatif digunakan untuk analisis data. Penelitian ini dilakukan menggunakan triangulasi sumber untuk mendapatkan data UKM yang lebih akurat. Hasil penelitian menunjukan bahwa pemangku kepentingan UKM perlu menerapkan strategi berikut untuk bertahan dari pandemi. Artinya menggunakan pemasaran melalui media sosial berupa Instagram, Facebook dan WhatsApp bekerjasama dengan pihak penyedia jasa transportasi online seperti Go-Food dan Grab-Food, inovasi dalam produk mereka.Kata Kunci: Strategi; Perekonomian; Pandemi; UKM.